Customization of Avatars in a HPV Digital Gaming Intervention for College-Age Males: An Experimental Study. (October 2018) - Darville, Gabrielle; Anderson – Lewis, Charkarra; Stellefson, Michael; Lee, Yu-Hao; MacInnes, Jann; Pigg, R. Morgan; Gilbert, Juan E.; Thomas, Sanethia
Background. Digital games are increasingly popular among college age men and present themselves as an ideal platform to deliverHPV interventions. Customizingavatars in role playing games encourage intrinsic motivation in the learning process because of self-representation.Proteus Effect research suggests that the representations people make are an adaption of their actual/ ideal self and dictate how one conforms to the expectations and identitycues of theiravatar . Objective/Purpose: This study evaluated the effectiveness of a digital gaming intervention aimed at increasingHPV risk perceptions, self- efficacy and behavioral intention to receive theHPV vaccine among college age men (18 - 26). Methods. This randomized control trial employed a 2 X 2 fully-crossed between subjects and tested the effects ofavatar characters (assigned/customized) and perception of self (ideal/actual) on HPV risk perception, HPV vaccine self-efficacy and behavioral intent to receive theHPV vaccine . Participants were randomly assigned to one of four conditions. Results. A Factorial ANOVA with repeated measures and a between subjects' factor (split plot) was used to test for the differences between the means of the outcome variables. Despite having no main or interaction effect our analysis did report a significant main effect of using a pre-post design with the experiment as a stimulus. Discussion/Conclusion. For experimental data, customizing anavatar to look like one's actual self increases risk perception for the HPV virus and self – efficacy for theHPV vaccine whereas customizing an avatar to look like one's ideal self increases one's intent to receive theHPV vaccine .